2019
DOI: 10.1089/mdr.2017.0351
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mismatch Amplification Mutation Assay PCR and PCR-Restriction Fragment Length Polymorphism for Detection of Major Mutations ingyrAandparCofEscherichia coliAssociated with Fluoroquinolone Resistance

Abstract: Fluoroquinolones are the drug of choice for most of the infections caused by Escherichia coli, and their indiscriminate use has resulted in increased selective pressure for antibiotic resistance. At present, sequencing is the only reliable and direct technique to detect mutations in the quinolone resistance determining region (QRDR). In this study, a rapid and reliable mismatch amplification mutation assay (MAMA) PCR to detect mutations in the QRDR was evaluated and compared to PCR-restriction fragment length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Pereira et al (2007) found only one isolate harbouring qnr among 144 ciprofloxacin‐resistant isolates (Pereira et al, 2007). This could be due to other resistance mechanisms such as QRDR mutations or overexpression of efflux pumps in fluoroquinolone‐resistant strains (Jazeela et al, 2019; Rezazadeh et al, 2016; Shetty et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pereira et al (2007) found only one isolate harbouring qnr among 144 ciprofloxacin‐resistant isolates (Pereira et al, 2007). This could be due to other resistance mechanisms such as QRDR mutations or overexpression of efflux pumps in fluoroquinolone‐resistant strains (Jazeela et al, 2019; Rezazadeh et al, 2016; Shetty et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…There was a positive correlation between iutA and biofilm formers and is in contrast to the observation by Naves et al (2008) who found no significance difference between the presence and absence of iutA with strong and weak biofilm formers (Naves et al, 2008). Most clinical isolates showed high resistance to ciprofloxacin and had gyrA and parC mutations while very few isolates were positive for plasmid‐mediated quinolone resistance determinants (Jazeela et al, 2019; Shetty et al, 2019). Most of the clinical isolates were able to transform from nonbiofilm former to biofilm former under in vitro gut conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of mutation in QRDR using mismatch amplification mutation-MAMA-PCR: A MAMA assay was performed on the 43 isolates to detect the point mutations in the QRDR16. The known point mutations at amino acid position 83 and 87 of gyr A, 80 and 84 of par C, 447 of gyr B and 416 amino acid position of parE were targeted17. The primers used in the study are outlined in Table I.…”
Section: Methodsmentioning
confidence: 99%
“…2). For detecting QRDR mutations, the method usually follows a duplex PCR technique wherein two bands can be obtained in wild type and a single band can be seen in mutant version same gene9.…”
Section: Primer Designing Protocolmentioning
confidence: 99%
“…Fluoroquinolones are synthetic class of antibacterials that act on both DNA gyrase and topoisomerase IV and have many clinical applications. Topoisomerases play a prominent role in DNA replication where DNA gyrase or topoisomerase II (2 gyrA and 2 gyrB subunits) introduces negative supercoils into DNA and topoisomerase IV (2 parC and 2 parE subunits) responsible for removing the interlinking structure between the two newly produced DNA strands during replication9. Mutations in the QRDR of bacterial pathogens inhibit the binding of fluoroquinolone to DNA and enzyme (topoisomerase targets) complex and are the major cause of fluoroquinolone resistance.…”
Section: Introductionmentioning
confidence: 99%